Addressing the complexity of medication use in older people with intellectual disability - O'CONNELL, JULIETTE ANNE (Trinity College Dublin. School of Pharmacy & Pharma. Sciences. Discipline of Pharmacy, 2019)
Background: People with intellectual disabilities (ID) experience high levels of polypharmacy and medication burden. Many of the most commonly occurring medical conditions in older adults with ID are treated with medications that have anticholinergic and/or sedative activity. The Drug Burden Index (DBI), Anticholinergic Cognitive Burden (ACB) Scale and Sedative Load Model are three tools which evaluate the burden of these types of medications on an individual. These measures have been found to be associated with poorer cognitive and physical performance in older adults without ID. However, little research has been carried out to date assessing these measures of drug burden in older adults with ID. Methods: Data for this study is drawn from Wave 2 (2013/2014) of the Intellectual Disability Supplement to the Irish Longitudinal Study on Ageing (IDS-TILDA), a representative population of people with ID aged 40 years and over in Ireland. Three inventories of medications were compiled and the DBI score, ACB score and Sedative Load score for each individual was calculated and analysed for associations using self- and objectively-reported data on medication use and physical health, including health conditions. Physical function measures were Barthel Index ADLs, grip strength and timed up and go. Frailty was measured using a modified version of Fried?s Frailty Phenotype. Multinomial logistic regression was used to evaluate the association between DBI score and potential adverse effects. Analysis of Covariance (ANCOVA) was used to evaluate the association between DBI score and physical function measures. Multinomial logistic regression was used to assess the association between polypharmacy, DBI, ACB and Sedative Load exposure and frailty using modified Fried?s Frailty Phenotype. Results: DBI exposure was found to be higher than that observed among older adults without ID. Multivariate regression found no statistically significant association between DBI and three potential adverse effects ? daytime dozing, chronic constipation or fall in the previous 12 months. ANCOVA found a significant association between DBI exposure and Barthel Index ADLs. No significant association was found between DBI score and performance in two objective measures of physical function, grip strength and TUG, using ANCOVA analysis. Excessive polypharmacy was found to be significantly associated with frailty in multivariate regression analysis. However, DBI, ACB and Sedative Load were not significantly associated with frailty. Conclusions: This is the first time DBI has been described in older adults with ID. Scores were much higher than those observed in the general population and higher scores were associated with higher dependence in Barthel Index activities of daily living. Grip strength and timed up and go scores were not significantly associated with DBI. Frailty was significantly associated with excessive polypharmacy, but not with DBI, ACB or Sedative Load. Future work will focus on other measures of drug burden and their association with functional decline in this population.
APPROVED
Keywords: pharmacy; medication; anticholinergic; sedative; drug burden index; intellectual disability; functional limitations; physical function; adverse effects; frailty; sedative load model; anticholinergic cognitive burden; ageing